Outcome of Trabeculectomy with Suprachoroidal Derivation: A Novel Glaucoma Procedure in Saudi Arabia - Alghamdi AS; Alotaibi HA; Bakr MA; Alshaibani AK; Alshamrani SM (Clinical Ophthalmology)
Abdullah S Alghamdi,1 Hammam A Alotaibi,1 Medhat A Bakr,2 Askar K Alshaibani,3 Saad Mosleh Alshamrani1 1Ophthalmology Department. Prince Sultan Military Medical City, Riyadh, Saudi Arabia; 2Ophthalmology Department, King Fahd Hospital of the University, Khobar, Saudi Arabia; 3Ophthalmology Department, Dhahran Eye Specialist Hospital, Dhahran, Saudi ArabiaCorrespondence: Askar K Alshaibani, Email Asker0908@gmail.comAim and Background: Trabeculectomy with suprachoroidal derivation (SCD) is a relatively new surgical technique developed by Rodolfo A. Perez et al and introduced in the literature in 2013. Two filtration mechanisms are used to decrease IOP. First, the classical route is created by trabeculectomy, where aqueous humor is drained from the anterior chamber via the subconjunctival fistula, and the second route utilizes the suprachoroidal space to filter aqueous through the uveoscleral mechanism.Objects: The objects of this article are to assess efficacy and safety of Trabeculectomy with Suprachoroidal Derivation procedure.Methods: This is a retrospective case series study aims to evaluate the outcomes and success rate trabeculectomy with suprachoroidal derivation procedure in patients with uncontrolled IOP in a tertiary hospital in Saudi Arabia.Results: The study included 59 patients (71 eyes) over a median 23 months follow-up period,  62% were males and 38% females, a statistically significant reduction of intraocular pressure and reduction of number of medication was noticed (p = 0.0001 and p = 0.0005, respectively) following the surgical intervention with a success rate of 77.5%.Conclusion: The surgical technique provides a safe and effective route for aqueous outflow in combination with standard filtration surgery.Clinical Significance: This study demonstrates the safety and potential efficacy of trabeculectomy with suprachoroidal derivation as a novel surgical technique for glaucoma control.Keywords: bleb complication, intraocular pressure, IOP, suprachoroidal derivation, suprachoroidal drainage, trabeculectomy